Tailoring Multi-Phenyl Ring Cation for Stable Scalable Hybrid Bismuth Iodide Amorphous Film Enabling Record Sensitivity and High-Performance X-Ray Array Imaging - Xu, Youkui (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.